New Analytical and Empirical Expressions for the Percentage of the Star's Flux Through TransparentAtmosphere Between Two Wave Lengths - Sharaf, Prof.Mohammed Adel; Mominkhan, Z.A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, new analytical and empirical expressions for the percentage of the star's flux through transparent atmosphere between two wave lengths are developed. For the analytical developments, literal expression of the percentage, A, of the total emitted flux from a star of temperature T radiates as black body is established in terms of the polyogarithm functions, together with the rate of change of A, with respect to T. For the computational developments, the maximum value of the percentage of the total flux MF in the region was computed togetherwith the corresponding temperature at the maximum percentage flux.The variations of the percentage of the total flux with temperature are displayed graphically for some values of Linear correlation coefficients between different attributes are also given. Finally, new empiricalrelation was developed between MF and , with complete error estimates These error estimates are ,the variance of the fit ,the variance of the least squares solutions vector, the average square distance between the exact and the least-squares solutions. Allthe precision criteria of this relationare very satisfactory.